Efficiency in stress echo service delivery without compromising on diagnostic accuracy: quality improvement project on the need to advise cessation of rate-controlling medication before dobutamine stress echocardiography - Emil Tom John; Laya Hariharan; Muhammad (Syed Zohaib) Amjad; Attila Kardos (Clinical Medicine)
Background: Stress echocardiography (SE) has been identified as an established non-invasive cardiac imaging for the detection of suspected myocardial ischaemia.1,2 SE protocols are variable across hospitals and countries in the recommendation of the cessation of rate-controlling medication (RCMx) before SE. There are recommendations advising the cessation of beta-receptor blockers (BB) and rate-controlling calcium-channel blockers (CCB) 48 h before SE to improve he diagnostic accuracy of the test.3 However, this approach may have implications for the efficient management of SE waiting lists and the abrupt cessation of these medications could lead to a haemodynamic rebound effect, potentially precipitating exacerbated angina or hypertension complications. Objective: To assess the efficacy of dobutamine SE (DSE) in a cohort of patients where discontinuation of RCMx was not required, we conducted a 1-year review of outcomes in individuals evaluated for suspected coronary artery disease (CAD) Method: 227 consecutive patients underwent DSE between January 2022 and January 2023 in a single centre. In addition to dobutamine, the protocol allowed the administration of intravenous atropine (maximum dose 1.2 mg), and ‘top-up’ handgrip exercise at the discretion of the performing cardiologist. We assessed the DSE outcome (positive vs negative), target (85% of maximum age predicted) heart rate (THR) and the achieved peak HR, in the two groups with RCMx and without (No-RCMx). We analysed the patients’ characteristics and 12-month outcome of a combined major adverse cardiac event of death, non-fatal MI, stroke, admission with angina and unplanned revascularisation (Fig 1). Results: Of the 227 patients, 59% were on No-RCMx (men: 49%). Eighty-eight percent of the patients in the RCMx group were on BB and 12% on other RCMx. THR was achieved in 74% of the RCMx and 90% in No-RCMx groups (p=0.001). Positive DSE was observed in 49% (46/93) of patients on RCMx vs 28% (38/134) on No-RCMx (p=0.001). Patients who did not reach THR (41% (15/37)) had positive DSE compared with 36% (69/190) who reached THR (p=0.626). There was no difference between groups in the peak wall motion score index (WMSI). Logistic regression analysis showed that THR was not an independent determinant of positive DSE (OR: 1.3, 95% CI 0.47–3.59, p=0.611), but being on RCMx was (OR 2.03, 95% CI 1.06–3.91, p=0.034). The MACE rate was higher in patients in whom THR was not achieved (10/37, 27.0%) vs where THR was achieved (12/190, 6.3%) (p<0.0001) in both the RCMx (8/24, 33% vs 8/69, 12%, p=0.015) and No-RCMx (2/12, 15% vs 4/121, 3%; p=0.045) groups, respectively. RCMx was a determinant of MACE (OR 3.67, 95% CI 1.04–13.02, p=0.043) (Table 1). Conclusion: This retrospective analysis of DSE data demonstrated comparable efficacy in patients with and without RCMx during evaluation for suspected coronary artery disease (CAD). The findings indicate that patients undergoing DSE while on RCMx can proceed without compromising test accuracy, while also avoiding the adverse effects associated with discontinuing RCMx, thereby enhancing the overall safety and tolerability of the procedure.